Internal and external loads in training week before the competition in U19 high-level soccer players - Martín-López, Á.; Mendes, R. S.; Castillo-Rodríguez, A. (The Journal of Strength and Conditioning Research, 2021)
Nowadays, the information about the load in training sessions (TRs) and the relationship of these TRs with official competition are necessary to gain the sport success in soccer. The aim of this study was to quantify the different loads in TRs according to days before the competition (P-4, P-2, and P-1) on soccer players U19 based on their playing position and their sport success. Twenty-four male Spanish high-level players (age: 16.5 ± 0.5 years; height: 1.69 ± 0.04 m; and body mass: 63.0 ± 6.3 kg) participated in the study. They were grouped according to their playing position: external defenders, internal defenders (ID), external midfielders, internal midfielders (IM), and forwards (FO). To conduct the study, global positioning system technology was used, and a 1-way analysis of variance and Pearson correlation were performed. The main results revealed that the highest physical and physiological responses in the TRs were shown by ID, IM, and players without sport success (p < 0.05), and during P-2. In addition, sport success is predicted by the mean heart rate (R2 = 0.33; p < 0.001). As conclusion, players covering central positions in the playing field performed higher physical and physiological demands than players covering exterior or forward positions. Furthermore, physical and physiological responses during the TRs P-2 may be similar to the responses produced in competition match and are notably different depending on the sport success of the soccer player.